1992
DOI: 10.1017/s0021932000006775
|View full text |Cite
|
Sign up to set email alerts
|

Birth Order and Health Status in a British National Sample

Abstract: Analysis of British National Child Development Study data corroborates the long held views that first born children tend to get more medical surveillance than those of later birth order, and that there is a direct relationship between achieved family size and social status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 11 publications
(12 reference statements)
2
21
0
Order By: Relevance
“…In line with this idea, primogeniture (first offspring inheritance) is widespread in human populations [for a review, see 38], and firstborns tend to end up in an advantaged position during upbringing with regard to both health [29], [62] and educational achievement [34], [63]. In accordance with this, our results showed that firstborn sons were those who gave birth to the largest numbers of offspring, and this is presumably because they began reproduction earlier.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with this idea, primogeniture (first offspring inheritance) is widespread in human populations [for a review, see 38], and firstborns tend to end up in an advantaged position during upbringing with regard to both health [29], [62] and educational achievement [34], [63]. In accordance with this, our results showed that firstborn sons were those who gave birth to the largest numbers of offspring, and this is presumably because they began reproduction earlier.…”
Section: Discussionsupporting
confidence: 85%
“…By contrast, later-born children can be out-competed for resources that are most critical in early childhood. For example, they are less likely than firstborns to attend infant clinics and to receive vaccination against childhood diseases [29], are more poorly nourished than firstborns [30], [31], and in large families, they run a higher risk of experiencing accidents during early childhood [32]. Associations between birth order and educational level have also been found; usually suggesting that firstborns are advantaged [28], [33][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Horton () finds that later‐born children in the Philippines received less nourishment than first‐born, as assessed through children's height and weight. A number of studies have found that in developed countries and developing countries, later‐born children are less likely to be vaccinated (Barreto and Rodrigues ; Kaplan, Mascie‐Taylor, and Boldsen ). First‐borns often have higher educational achievements than subsequent siblings (Black, Devereux, and Salvanes ; Conley and Glauber ).…”
mentioning
confidence: 99%
“…A previous study using the same data base (Kaplan and Mascie-Taylor 1991) shows that various childhood disease frequencies relate to birth order. In this study it was found that first born are more likely to receive the requisite number of immunizations, to be cared for in age-graded specialty clinics, to have fewer long absences from school, and to have a better socio-economic environment in which to develop than do children born later in the mother's reproductive life span, although first and second born children in more affluent families are more prone to early childhood asthma.…”
mentioning
confidence: 90%